2013
DOI: 10.1007/s00300-013-1337-1
|View full text |Cite
|
Sign up to set email alerts
|

Year-round acoustic detection of bearded seals (Erignathus barbatus) in the Beaufort Sea relative to changing environmental conditions, 2008–2010

Abstract: 192 Hz. Spectrograms of acoustic data were examined for characteristic patterns of bearded seal vocalizations. For each recorder, the number of hours per day with vocalizations was compared with in situ water temperature and satellite-derived daily sea ice concentrations. At all sites, bearded seals were vocally active yearround. Call activity escalated with the formation of pack ice in the winter and the peak occurred in the spring, coinciding with mating season and preceding breakup of the sea ice. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 47 publications
6
29
1
Order By: Relevance
“…In contrast, heavy ice conditions with reduced open water have been shown to reduce vocalization rates of roaming males occupying pack ice near shore in Svalbard and Alaska (Van Parijs, 2004;Jensen, 2005). Our results correspond with the finding of MacIntyre et al (2013) that bearded seals offshore in the Beaufort Sea were detected more often in the highest sea ice concentrations. This finding suggests that bearded seals may be overwintering in the offshore environment.…”
Section: Relation Of Ice Seal Acoustic Presence and Sea Icesupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast, heavy ice conditions with reduced open water have been shown to reduce vocalization rates of roaming males occupying pack ice near shore in Svalbard and Alaska (Van Parijs, 2004;Jensen, 2005). Our results correspond with the finding of MacIntyre et al (2013) that bearded seals offshore in the Beaufort Sea were detected more often in the highest sea ice concentrations. This finding suggests that bearded seals may be overwintering in the offshore environment.…”
Section: Relation Of Ice Seal Acoustic Presence and Sea Icesupporting
confidence: 92%
“…Trills were most common from March through June and present as early as December and January. In a multi-year acoustic study in the Alaskan Beaufort, MacIntyre et al (2013) found that bearded seals called throughout the winter. Our results show similar patterns of presence during winter, increasing through spring.…”
Section: Seasonal Presence and Variation In Acoustic Repertoirementioning
confidence: 99%
See 2 more Smart Citations
“…Continuous data on species presence are not possible for other survey methods, such as visual surveys, in the Arctic due to sea ice. Indeed, PAM has been used throughout other areas of Arctic North America for monitoring marine mammals, including the Bering Sea (Moore et al 2006;Munger et al 2008;Stafford et al 2010), western Beaufort Sea (Moore et al 2006;Hauser et al 2017a), Chukchi Sea (Delarue et al 2009;Blackwell et al 2012;Hannay et al 2013;Jones et al 2014;Clark et al 2015;Frouin-Mouy et al 2016), and Baffin Bay (FrouinMouy et al 2017;Marcoux et al 2017), and acoustic monitoring has even been used successfully as a tool for studying the distribution of seals under the ice in the winter (Calvert and Stirling 1985;Cleator and Stirling 1990;MacIntyre et al 2013;Jones et al 2014;Frouin-Mouy et al 2016). …”
Section: Introductionmentioning
confidence: 99%